Impact of Common Dizziness Associated Symptoms on Dizziness Handicap in Older Adults - Prell, Tino; Wassermann, Alexander; Zipprich, Hannah M.; Finn, Sigrid; Axer, Hubertus (Frontiers in Neurology, 2021)
Background: A cross-sectional observational study was designed to determine the impact of dizziness associated symptoms on the dizziness handicap inventory (DHI) in older adults (≥60 years). Methods: In total, 785 individuals referred to a multidisciplinary dizziness unit were assessed. Participants completed self-report questionnaires with general questions about symptoms of dizziness as well as the DHI. The DHI subscores (physical, functional, emotional) were calculated. Medical diagnoses were collected from the medical records of the patients. One-way MANOVA and networking analysis were used to analyze the impact of dizziness associated symptoms on dizziness handicap. Results: Most patients reported swaying dizziness (60.6%) and feeling of unsteadiness (59.8%) with substantial overlap between the types of dizziness. Most frequent dizziness associated symptoms were ear noise/tinnitus, visual problems, and nausea/vomiting. Network analysis revealed that visual disturbances, headache, and hearing impairment were associated with higher DHI and explained 12% of the DHI variance in the linear regression. In the one-way MANOVA visual problems and headache had an effect on all three DHI subscores, while hearing impairment was associated with the functional and emotional subscores of DHI. Conclusion: Distinct dizziness associated symptoms have substantial impact on dizziness handicap in older adults. A multifactorial assessment including these symptoms may assist in tailoring therapies to alleviate dizziness handicap in this group.